2015
DOI: 10.1039/c5cp03751d
|View full text |Cite
|
Sign up to set email alerts
|

Six-fold-symmetry internal rotation in toluenes: the low barrier challenge of 2,6- and 3,5-difluorotoluene

Abstract: Pure six-fold symmetry (V 6 ) internal rotation poses significant challenges to experimental and theoretical determination, as the very low torsional barriers result in huge tunneling splittings difficult to identify and to model. Here we resolved the methyl group internal rotation dynamics of 2,6-and 3,5-difluorotoluene using a newly developed computer code especially adapted to V 6 problems. The jet-cooled rotational spectra of the title molecules in the 5-25 GHz region revealed internal rotation tunneling d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It is known that there is a negligible barrier to the internal rotation of CH 3 in toluene 25 while the addition of substituents to the benzene ring introduces an asymmetry into molecular orbitals that leads to an increased barrier. 26–29 The ( V 3 ) barrier to internal rotation of CH 3 has been determined for different structural isomers of methylthiazole, 30–32 methyloxazole 33 and methylimidazole. 9 The magnitude of the parameter depends on the asymmetry of the molecular orbitals with which the CH 3 group interacts.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that there is a negligible barrier to the internal rotation of CH 3 in toluene 25 while the addition of substituents to the benzene ring introduces an asymmetry into molecular orbitals that leads to an increased barrier. 26–29 The ( V 3 ) barrier to internal rotation of CH 3 has been determined for different structural isomers of methylthiazole, 30–32 methyloxazole 33 and methylimidazole. 9 The magnitude of the parameter depends on the asymmetry of the molecular orbitals with which the CH 3 group interacts.…”
Section: Resultsmentioning
confidence: 99%
“…Only in 2,6-difluorotoluene, the potential is V 6 due to symmetry. [13] As mentioned, the barrier hindering a methyl rotation is quite sensitive to many structural and electronic effects. In a systematic investigation on a series of methyl alkyl ketones, Andresen et al proposed a link between the torsional barrier of the acetyl methyl group and the molecular structure at the other side of the carbonyl bond.…”
Section: Discussionmentioning
confidence: 98%
“…(1) 26DMFB (this work), (2) 2-fluorotoluene, [6] (3) 2,4,5-trifluorotoluene, [14] (4) 2,3,4trifluorotoluene, [14] (5) 2,3-difluorotoluene, [9] (6) 2,4-difluorotoluene, [10] (7) 2,5difluorotoluene, [11] and (8) 2,6-difluorotoluene. [13]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is seen in the change of the potential barrier of toluene for various levels of halogenation around the benzyl ring. In toluene, the V 6 barrier is reported as 4.837920599(11) cm −1 ,[2] and increases for p-chlorotoluene (4.872(14) cm −1 )[3], 3,5-difluorotoluene (7.156(84) cm −1 )[4] and 2,4-difluorotoluene (12.432(20) cm −1 ), [4] but decreases slightly for p-fluorotoluene (4.8298(64) cm −1 ) [5]. In a more recent study, an investigation of p-halotoluenes found a p-chlorotoluene V 6 barrier of 4.836(29) cm −1 , which was also found to be a good barrier to describe the tunneling motion in p-bromotoluene and p-iodotoluene.…”
Section: Introductionmentioning
confidence: 99%